2023
DOI: 10.1002/mop.33676
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable phase gradient metasurface antenna for beam steering

Abstract: In this article, a reconfigurable phase gradient metasurface (PGM) antenna for beam steering is presented. The antenna consists of a three‐layer transmitarray metasurface and a broadband patch antenna. The PIN diode is loaded onto the split ring resonator (SRR). The phase gradient principle is used to regulate the electromagnetic waves to achieve the function of the gain enhancement and beam tilt. By clever design, the antenna is quickly switched in beam tilt in the 8.9–9.9 GHz range and gain enhancement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Figure 2 a, b show the two commonly used schematic frameworks for the conventional RISs: the stacked multilayer RIS 44 , 45 , 52 54 and receiver-transmitter RIS 38 42 . Based on the concept of frequency-selective-surface (FSS), the stacked multilayer RIS can exhibit satisfactory phase-shifting property performance, but the high profile makes it less preferred in wireless communication systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 a, b show the two commonly used schematic frameworks for the conventional RISs: the stacked multilayer RIS 44 , 45 , 52 54 and receiver-transmitter RIS 38 42 . Based on the concept of frequency-selective-surface (FSS), the stacked multilayer RIS can exhibit satisfactory phase-shifting property performance, but the high profile makes it less preferred in wireless communication systems.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio BW/BW3dB is used to evaluate the operating BW as a percentage of BW3dB. It can be observed that the BW/BW3dB of the stacked multilayer RIS is very small because the operating BW is much narrower than BW3dB 44 , 45 , 52 54 . Compared with them, the proposed RIS has a much larger BW/BW3dB value of 96%, suggesting a very narrow occupied bandwidth.…”
Section: Resultsmentioning
confidence: 99%
“…1 Compared to the traditional metal reflector and phased array, planar RA has the advantages of low profile, [2][3][4] high gain, [5][6][7] low cost, 8 simple deployment and mobility, and is widely used in automotive/airborne radar, 9 satellite/space communication, 10,11 low-cost beam steering 12,13 and many other fields. The majority of existing RA designs are linearly polarized (LP) [8][9][10][11][12][13] and are susceptible to electromagnetic interference and multipath effect caused by complex environment, which easily leads to polarization misalignment and power transmission loss. 14,15 This problem can be effectively prevented by circularly polarized (CP) antennas due to the robustness of circular polarizations against environmental interferences.…”
Section: Introductionmentioning
confidence: 99%